2021
DOI: 10.3389/fpls.2021.739671
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of the Plant U2 snRNP Auxiliary Factor Large Subunit A Gene Family in Response to Developmental Cues and Environmental Stimuli

Abstract: In all organisms, splicing occurs through the formation of spliceosome complexes, and splicing auxiliary factors are essential during splicing. U2AF65 is a crucial splicing cofactor, and the two typical RNA-recognition motifs at its center recognize and bind the polypyrimidine sequence located between the intron branch site and the 3′-splice site. U2AF65A is a member of the U2AF65 gene family, with pivotal roles in diseases in mammals, specifically humans; however, few studies have investigated plant U2AF65A, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…The growth and stress treatments of NIP were performed according to the procedure published by Lu et al [ 55 ] with minor modifications. Seedlings were cultivated hydroponically with Mucun B nutrient solution, in a climate chamber (QY-14; Quanyou Electronic Technology Co., Ltd., Nanjing, China) at 22 °C/20 °C under a 16 h/8 h light/dark cycle at a light intensity of 100 μmol m −2 s −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The growth and stress treatments of NIP were performed according to the procedure published by Lu et al [ 55 ] with minor modifications. Seedlings were cultivated hydroponically with Mucun B nutrient solution, in a climate chamber (QY-14; Quanyou Electronic Technology Co., Ltd., Nanjing, China) at 22 °C/20 °C under a 16 h/8 h light/dark cycle at a light intensity of 100 μmol m −2 s −1 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we also found that U2 snRNP auxiliary factor encoding gene, U2AF65A ( MSTRG.17488 ), was DAS by A3SS event under 4 h of cold. OsU2AF65A was certificated to mediate response to various stresses, such as drought, cold, high salt, and heavy metal exposure in rice ( Lu et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…OsU2AF65A was certificated to mediate response to various stresses, such as drought, cold, high salt, and heavy metal exposure in rice (Lu et al, 2021).…”
Section: The Roles Of Rbps In Response To Abiotic Stressmentioning
confidence: 99%
“…The CDS of OsU2B″ (LOC_Os03g18720.1) was amplified using gene-specific primers (5'-CCT GTT GTT TGG TGT TAC TTA AGC TTA TGT TGT CCG GCG ACA TACC-3' and 5'-TCC TCG CCC TTG CTC ACC ATG GAT CCT CAC TTC TTT GCG TAG GAT ATA GCC-3') and inserted into the GFP (pGreen II-UBI-GFP) vector to generate a fusion construct according to Lu et al [1]. NLS − mCherry (SV40 large − T antigen NLS, a signal peptide guiding GFP into the nucleus) was selected as a marker for nuclear localisation [54].…”
Section: Subcellular Localisationmentioning
confidence: 99%
“…In contrast to the model of the 1 gene-1 polypeptide in prokaryotes, eukaryotic genes contain exons and introns. They generate mature mRNAs via splicing, which is an important post-transcriptional regulatory link during pre-mRNA splicing [ 1 ]. In the splicing process, the U1 snRNP identifies and binds to the 5'-terminal splicing site of the intron [ 2 ].…”
Section: Introductionmentioning
confidence: 99%